Customer satisfaction, service quality, and customer value: years 2000-2015. Issue 1 (9th January 2017) - Oh, Haemoon; Kim, Kawon
Abstract : Purpose: This paper aims to review hospitality and tourism research on customer satisfaction (CS), service quality (SQ) and customer value (CV) published in several established hospitality and tourism journals over the past 15-16 years. A parallel review of research on the same topics published in several leading marketing journals is also conducted to show comparisons in research trends across the two different, but closely related, fields of study. By doing so, this paper aims to summarize lessons learned from previous research and provide suggestions for future research on the topics in the hospitality and tourism discipline. Design/methodology/approach: This study reviewed 242 articles appearing in six selected hospitality and tourism journals and 71 articles in four business journals that were published on CS, SQ and CV over the period of 2000-2015. A comprehensive coding scheme was developed to sort each study by more than 50 criteria. Findings: While research on these topics has grown constantly during the period in the hospitality and tourism field, it has declined in the general business discipline over the same period. Hospitality and tourism research relied heavily on cross-sectional data through a survey approach, whereas business studies used experimental designs more frequently. Research on CS has sustained both interest and productivity, but research on SQ and CV has dwindled over time. Another notable finding is that most studies are not grounded in strong theories, although CS studies tended to be more theory-embedded. Practical implications: This study provides many useful insights into the research practice and trends of related research and suggestions for future research, especially for hospitality and tourism researchers. Originality/value: This study provides an unprecedented, comprehensive review of theories, methods, discussion points, implications, limitations and conclusions of studies on CS, SQ and CV published in selected hospitality and tourism journals over the past 15 years.